1987
DOI: 10.1108/eb051645
|View full text |Cite
|
Sign up to set email alerts
|

Assumptions, Culture and Performance Appraisal

Abstract: Cultural assumptions are often inadvertently exported or imported when performance appraisal is introduced in organisations in developing countries. Performance appraisal has been developed in “individualist” societies, and the systems, when applied in non‐individualistic cultures, can cause unintended offence, or are incorrectly, and therefore uselessly, employed. Guidelines for the design of more culturally appropriate approaches are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…Swedes viewed their managers as problem-solvers while the Italians viewed their managers as model experts. Seventy-eight percent of Japanese managers agreed with the same statement, i.e., managers should be experts (Seddon, 1987). Performance appraisal as a means of developing influence over subordinates is only partially supported.…”
Section: Trust and Confidence In Subordinatesmentioning
confidence: 95%
“…Swedes viewed their managers as problem-solvers while the Italians viewed their managers as model experts. Seventy-eight percent of Japanese managers agreed with the same statement, i.e., managers should be experts (Seddon, 1987). Performance appraisal as a means of developing influence over subordinates is only partially supported.…”
Section: Trust and Confidence In Subordinatesmentioning
confidence: 95%
“…Seddon (1987) reported that respondents in societies high in uncertainty avoidance adopt face-saving strategies to avoid embarrassment when the appraisal is negative. Our findings do not support this conclusion because notions of face saving, harmony, or reciprocation of favors are not very important, and may even be irrelevant, in a competitive work environment.…”
Section: Resultsmentioning
confidence: 97%
“…Another important objective of the appraisal review in Canada (Stone & Meltz, 1992) and the U.S. (Seddon, 1987) is to provide a formal opportunity for subordinates to give feedback or express their views to their supervisors. U.S. employees often feel they do not have much opportunity to discuss their career or personal needs and the appraisal review meeting does provide a once-a-year opportunity for the employees to discuss their views and feelings (Milliman, Nathan, & Mohrman, 1991).…”
Section: Subordinate Expressionmentioning
confidence: 99%